Preparation method and application of fine blasting bead for cigarette filter tip
By accurately controlling the wall and core material preparation process of small blasting beads, combined with automated implantation and precision sealing technology, the problem of insufficient quality and stability of blasting beads in the existing technology is solved, and higher quality and stable blasting beads are achieved, and the taste and shelf life of cigarette products are improved.
Patent Information
- Application Number
- CN202510140654.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-22
AI Technical Summary
The existing preparation methods for small burst beads and their application technologies in cigarette mouth rods have problems such as inaccurate wall preparation, unstable core composition, insufficient particle size control, inefficient application process and unstable storage performance, resulting in insufficient quality and stability of burst beads, which affects the taste and shelf life of cigarette products.
By accurately controlling the raw material selection and preparation process, including the ratio of wall materials to core materials, dissolution and mixing conditions, etc., we ensure that the wall material of the blasting bead is regular and the core material composition is stable. Automatic implantation and precision sealing technology are adopted to achieve stable installation and efficient release of blasting beads in the mouth rod, and the cracking pressure and breathability are precisely controlled through micro pressure sensors and laser hole drilling technology.
It significantly improves the quality and stability of the blasting beads, improves the uniformity of cracking and consistency of taste, extends the shelf life of cigarette products, and enhances market competitiveness.
Smart Images

Figure BDA0005264737140000101 
Figure BDA0005264737140000111 
Figure BDA0005264737140000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of fine bursting beads for cigarette mouthpieces, in particular to a preparation method of fine bursting beads for cigarette mouthpieces and application thereof. Background Art
[0002] In the field of cigarette manufacturing, small bursting beads are an important element to improve the taste and quality of cigarettes, and their preparation methods and application technologies have always received widespread attention. However, the existing preparation methods of small bursting beads and their application technologies in cigarette mouthpieces still have many shortcomings and urgently need to be improved.
[0003] First of all, from the perspective of the preparation process of the popping beads, the traditional preparation methods have obvious defects in the selection and preparation of wall materials and core materials. The wall material, as the outer shell of the popping beads, directly affects the overall performance of the popping beads through its quality and stability. However, the preparation of wall materials in the prior art often lacks precise control, resulting in a loose wall material structure, unclear layers, and the presence of multiple large holes. These defects will seriously affect the bursting pressure and storage stability of the popping beads. At the same time, there are also problems such as uneven mixing and insufficient purity in the preparation process of the core material, which leads to unstable composition and properties of the core material, thereby affecting the release effect and taste of the popping beads in the cigarette mouthpiece.
[0004] Secondly, in terms of the particle size control of the popping beads, the existing technology also has significant deficiencies. The distribution and uniformity of the particle size are crucial for the application of the popping beads in the cigarette mouthpiece. However, traditional preparation methods often make it difficult to accurately control the particle size of the popping beads, resulting in a particle size distribution range that is too wide and the presence of a large number of particles whose particle sizes deviate from the set range. This will not only affect the arrangement and distribution of the popping beads in the cigarette mouthpiece, but also reduce the uniformity of the bursting beads and the consistency of the taste.
[0005] In addition, in the application process of popping beads, the existing technology also has many problems. For example, the implantation method of the popping beads is often not efficient and precise enough, resulting in inaccurate positioning of the popping beads in the cigarette mouthpiece, affecting the smoker's experience. At the same time, the control of the bursting pressure of the popping beads is not precise enough. Some popping beads will burst under too little pressure, while some popping beads need to be under too much pressure to burst, which will reduce the release effect and taste stability of the popping beads. In addition, there is a lack of effective methods and means to adjust the air permeability of the cigarette mouthpiece, which limits the release of the popping bead flavor.
[0006] In terms of long-term storage, the popping beads of the prior art are also prone to deterioration and performance degradation. Due to defects in the preparation of wall materials and core materials and insufficient control of particle size, the popping beads are prone to rupture and leakage during storage, resulting in a shortened shelf life and deterioration in quality. This will not only affect the quality and taste of cigarette products, but also increase production costs and waste resources.
[0007] In summary, the existing method for preparing fine bursting beads and the application technology in cigarette mouthpieces have many shortcomings and defects, including inaccurate preparation of wall materials and core materials, insufficient control of particle size, inefficient application process and unstable long-term storage performance. These defects seriously limit the application and development of fine bursting beads in the field of cigarette manufacturing. Therefore, there is an urgent need for a new method for preparing fine bursting beads and application technology to solve the above problems, improve the quality and stability of the bursting beads, and meet the high quality requirements of cigarette production for bursting beads. Summary of the invention
[0008] Technical issues solved
[0009] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for preparing fine bursting beads for cigarette mouthpieces and applications thereof. The method for preparing fine bursting beads for cigarette mouthpieces and product applications thereof provided by the present invention ensure the regularity of the wall material structure of the bursting beads and the stability of the core material components by precisely controlling the raw material selection and preparation process, including the ratio of wall material and core material, dissolution and mixing conditions, etc., thereby greatly improving the consistency and storage stability of the bursting beads and reducing the rupture rate and leakage rate. The present invention also optimizes the application technology of the bursting beads in the cigarette mouthpiece, and realizes the stable installation and efficient release of the bursting beads in the mouthpiece through automated implantation and precision sealing technology, thereby bringing a unique flavor experience to smokers, while ensuring the excellent taste and long-term quality of the cigarette products.
[0010] Technical Solution
[0011] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0012] In a first aspect, a method for preparing fine explosive beads for cigarette mouthpieces comprises the following steps:
[0013] First, chitosan and sodium alginate were selected as wall materials, accurately weighed in a mass ratio of 2:3, chitosan was dissolved in 1% acetic acid solution, stirred and dissolved at a temperature of 55°C at a speed of 350 rpm for 2.5 hours to ensure that chitosan was fully dissolved, and sodium alginate was dissolved in deionized water, the water temperature was controlled at 45°C, and stirred at a speed of 280 rpm for 3 hours to make it completely dissolved, then the two solutions were mixed and stirred at a stirring speed of 400 rpm for 20 minutes, and for the core material, spearmint oil and glycerol were selected and mixed at a mass ratio of 1:3 at a stirring speed of 280 rpm for 12 minutes;
[0014] Next, the prepared core material was added to the wall material solution, and an emulsification device equipped with a six-blade turbine stirring blade was used, with the ratio of the blade diameter to the reaction vessel diameter being 1:5, and the emulsification was performed at a stirring speed of 700 rpm for 18 minutes, and the temperature during the emulsification process was maintained at 38°C;
[0015] Subsequently, calcium chloride with a mass 0.25 times that of the wall material was added to the emulsion as a curing agent at a rate of 25 drops / minute, and the pH value of the reaction system was adjusted to 6.0. The reaction was stirred at 180 rpm at 28°C for 3.5 hours to prepare fine explosive beads with a particle size in the range of 0.5-2.0 mm.
[0016] Furthermore, when chitosan is pretreated before mixing with the wall material, the acetic acid solution needs to be purified by secondary distillation, and its purity needs to reach more than 99.5%. During the dissolution process, the temperature is maintained at 55±2°C by a stirring device with temperature feedback, and the stirring speed fluctuation range is controlled within ±15 rpm;
[0017] For sodium alginate, the water used for dissolution must be ultrapure water treated with ion exchange resin, with a conductivity of less than 2μS / cm. During dissolution, the container must be sealed with a stirring device to prevent water evaporation and impurities from mixing in, and the temperature must be maintained at 45±1℃;
[0018] When mixing two wall materials, a double planetary mixing device is used. The revolution speed of the stirring blade is 420 rpm and the rotation speed is 550 rpm. The mixing time is precisely controlled at 20±1 minute to ensure that the wall materials are evenly mixed, laying the foundation for the subsequent formation of a stable wall material structure.
[0019] Furthermore, the spearmint oil in the core material is extracted from the spearmint by supercritical carbon dioxide extraction, the spearmint is crushed to 40 mesh, loaded into an extraction kettle, and extracted for 3 hours with carbon dioxide as an extractant under the conditions of a pressure of 20 MPa and a temperature of 45° C. The spearmint oil obtained by the extraction is refined by molecular distillation at a distillation temperature of 70° C. and a pressure of 0.1 kPa to remove impurities;
[0020] Glycerol should be a food grade product with a purity greater than 99.8%. When mixing spearmint oil and glycerol, use a high shear dispersing emulsifier to assist in stirring at a speed of 3000 rpm. Mix at a stirring speed of 280 rpm for 12±0.5 minutes to ensure that the core material is uniform and stable.
[0021] Furthermore, the emulsification equipment is equipped with an intelligent variable frequency speed regulation system, which can adjust the stirring speed according to the real-time viscosity of the emulsion. When the viscosity of the emulsion is in the range of 0.6-1.2 Pa·s, the stirring speed is automatically maintained at 700±25 rpm. When the viscosity of the emulsion exceeds 1.2 Pa·s, the stirring speed is automatically increased to 750 rpm.
[0022] The temperature control system of the emulsification equipment adopts fuzzy control algorithm, with a temperature control accuracy of ±0.3℃. The reaction vessel adopts a three-layer jacket structure, with circulating water in the middle layer and insulation materials in the inner and outer layers to ensure stable temperature control. At the same time, during the emulsification process, the particle size of the emulsion is tested every 4 minutes. If the particle size deviation exceeds the set range of ±8%, it is corrected by adjusting the stirring speed, temperature or adding an appropriate amount of dispersant to ensure the formation of an emulsion with uniform and stable particle size.
[0023] Furthermore, the concentration of the curing agent calcium chloride is 30%, which needs to be diluted to 15% with deionized water before dropping. During the dropping process, the dropping speed is accurately controlled by a high-precision metering pump. The flow rate of the metering pump is set to 3mL / min, corresponding to a dropping speed of 25±2 drops / minute;
[0024] After adding the curing agent, the pH value of the reaction system was adjusted to 6.0±0.1 using 0.15 mol / L hydrochloric acid or sodium hydroxide solution. During the reaction, the temperature was maintained at 28±1°C by heating in an oil bath, and a variable frequency stirrer was used to continuously stir at a speed of 180±10 rpm for 3.5 hours;
[0025] After the reaction was completed, the beads were collected by vacuum filtration with the vacuum degree controlled at -0.08 MPa for 15 minutes, and then washed 4 times with anhydrous ethanol to remove the curing agent and impurities remaining on the surface.
[0026] In the second aspect, the fine bursting beads for cigarette mouthpieces prepared by the method for preparing fine bursting beads are characterized in that, through observation by scanning electron microscope, the bursting bead wall material presents a regular layered structure, each layer thickness is between 30-50 nanometers, the overall thickness of the wall material is uniform, the average thickness is 90±12 microns, and under observation under a high-resolution microscope, there are no holes or defects with a diameter greater than 8 nanometers inside the wall material;
[0027] The particle size of the popping beads was tested using a laser particle size analyzer, and the proportion of popping beads with a particle size range of 0.5-2.0mm reached more than 99%, and the standard deviation of the particle size distribution was less than 0.15mm, ensuring the high consistency and stability of the popping beads during the application of cigarette mouthpieces.
[0028] Furthermore, the content of spearmint oil in the popping bead core material is 25±2%, and the content of glycerol is 75±2%. The core material components are analyzed by gas chromatography-mass spectrometry, and the content of carvone in spearmint oil accounts for 65±3%. The melting point of the core material is -8±2°C and the boiling point is 190±5°C detected by differential scanning calorimeter. These physical properties ensure that the core material can be stably stored inside the popping bead at room temperature. During the smoking process of the cigarette, when the temperature reaches 320-420°C, the spearmint oil can be quickly released, bringing a unique cool flavor experience to the smoker.
[0029] In the third aspect, a method for applying fine popping beads for cigarette mouthpieces to cigarette mouthpieces is provided. In the production process of cigarette mouthpieces, an automated popping bead implantation production line is used, and the production line is equipped with a high-precision visual recognition robot arm and a high-speed positioning platform;
[0030] The repeatability of the robotic arm is ±0.08mm. An elliptical cavity with a diameter of 2.3±0.08mm is pre-set inside the cigarette mouthpiece to accommodate the popping beads. The robotic arm quickly and accurately identifies the position of the mouthpiece cavity through a visual recognition system and implants the popping beads into the cavity at a speed of 60 beads / minute.
[0031] After implantation, the opening of the mouthpiece cavity is sealed with thermoplastic polyurethane elastomer. The melt index of the thermoplastic polyurethane elastomer is 15g / 10min. The coating operation is carried out at 160°C with a coating thickness of 0.35±0.05mm, ensuring that the popping bead is well sealed inside the mouthpiece and can smoothly release flavor substances when the smoker squeezes the popping bead.
[0032] Furthermore, when the smoker squeezes the popping bead, it must break under a pressure of 2.5-3.5N to release the core material. The extrusion pressure is monitored in real time by integrating a micro pressure sensor on the cigarette mouthpiece. The accuracy of the pressure sensor is ±0.08N, and the air permeability of the mouthpiece is adjusted by laser drilling on the circumference of the mouthpiece. The diameter of the micropores is 0.12-0.22mm, and there are 6-9 micropores per square centimeter. Using an air permeability tester to test, the air permeability of the mouthpiece is between 32-42CU. After being stored for 8 months at a temperature of 26±2℃ and a humidity of 62±5%, sampling tests showed that the rupture rate of the popping bead was less than 1.5%, and the leakage rate was less than 0.8%. No obvious deterioration occurred, ensuring the high quality and long shelf life of the cigarette products.
[0033] Beneficial Effects
[0034] Compared with the known public technology, the technical solution provided by the present invention has the following advantages:
[0035] Beneficial effects:
[0036] 1. The method for preparing fine bursting beads for cigarette mouthpieces of the present invention significantly improves the quality and stability of the bursting beads by accurately controlling the selection and preparation process of the wall material and the core material. The wall material adopts high-purity chitosan and sodium alginate, and undergoes strict dissolution and mixing processes to form a regular and uniform layered structure, which effectively avoids the generation of holes and defects. The core material is made of advanced carbon dioxide supercritical extraction and molecular distillation refining technology to ensure the purity and stability of spearmint oil, and the mixing with propylene glycol also achieves a high degree of uniformity. This preparation method significantly improves the application performance of the bursting beads in cigarette mouthpieces, including the bursting pressure, particle size distribution, storage stability and other aspects of the bursting beads are superior to traditional preparation methods, bringing smokers a more high-quality and stable cool flavor experience.
[0037] 2. The present invention proposes an efficient method for applying tiny bursting beads to cigarette mouthpieces. Through an automated bursting bead implantation production line and a high-precision visual recognition robotic arm, rapid and accurate implantation of the bursting beads in the cigarette mouthpiece is achieved. At the same time, a thermoplastic polyurethane elastomer is used to seal the mouthpiece cavity opening to ensure the stability and sealing of the bursting beads inside the mouthpiece. In addition, the present invention also integrates micro pressure sensors and laser drilling technology to precisely control the bursting pressure of the bursting beads and the air permeability of the mouthpiece, further improving the smoking taste and flavor release effect of the cigarette. In terms of long-term storage, the bursting beads prepared by the present invention exhibit excellent stability and low leakage rate, effectively extending the shelf life of cigarette products and improving market competitiveness. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The present invention will be further described below in conjunction with the embodiments.
[0040] Example 1
[0041] (I) Material preparation:
[0042] Wall material:
[0043] High-purity chitosan (deacetylation degree ≥ 90%) and sodium alginate (viscosity 200-400 mPa·s) are selected as wall materials and accurately weighed according to a mass ratio of 2:3. The 1% acetic acid solution required for chitosan is purified by secondary distillation to a purity of more than 99.5%. Chitosan is slowly added to the acetic acid solution and placed in a stirring device with temperature feedback. It is stirred and dissolved for 2.5 hours at 55° C. (temperature fluctuation is controlled at ±2° C.) and 350 rpm (speed fluctuation range is ±15 rpm) to ensure that the chitosan is fully dissolved and the solution is uniform and transparent.
[0044] Sodium alginate was dissolved in ultrapure water (conductivity less than 2 μS / cm) treated with ion exchange resin. A sealed container with a stirring device was used. The water temperature was maintained at 45°C (±1°C) and stirred at 280 rpm for 3 hours until the sodium alginate was completely dissolved and no particles remained in the solution.
[0045] Core material:
[0046] Spearmint oil is extracted from fresh spearmint plants by supercritical carbon dioxide extraction. The spearmint is crushed into 40 mesh and then loaded into an extraction kettle. Under the conditions of pressure of 20MPa and temperature of 45°C, extraction is carried out for 3 hours with carbon dioxide as the extractant. The spearmint oil obtained by extraction is refined by molecular distillation at a distillation temperature of 70°C and a pressure of 0.1kPa, and is set aside after impurities are removed.
[0047] Use food-grade glycerol with a purity greater than 99.8%. When mixing spearmint oil and glycerol, use a high-shear dispersing emulsifier to assist stirring (speed 3000 rpm). Mix the two at a mass ratio of 1:3 at a stirring speed of 280 rpm for 12 minutes to ensure that the core material is uniform and stable, and the solution after mixing is clear and has no stratification.
[0048] (II) Emulsification process:
[0049] The prepared core material is slowly added to the wall material solution, and an emulsification device equipped with a six-blade turbine stirring blade (the ratio of the blade diameter to the reaction vessel diameter is 1:5) and an intelligent variable frequency speed regulation system and a fuzzy control algorithm temperature control system (the temperature control accuracy is ±0.3°C, the reaction vessel adopts a three-layer jacket structure, the middle layer is circulating water, and the inner and outer layers are insulation materials) is used. The equipment is started. When the viscosity of the emulsion is in the range of 0.6-1.2 Pa·s, the stirring speed is automatically maintained at 700 rpm (±25 rpm), and the temperature of the emulsification process is maintained at 38°C. The particle size of the emulsion is detected once every 4 minutes using a laser particle size analyzer. If the particle size deviation exceeds ±8% of the set range, it is corrected by adjusting the stirring speed, temperature or adding an appropriate amount of dispersant (such as polyvinyl alcohol, the added amount does not exceed 0.5% of the mass of the emulsion). The emulsification time is 18 minutes to ensure the formation of an emulsion with uniform and stable particle size.
[0050] (III) Curing and molding:
[0051] Calcium chloride with a concentration of 30% was selected as a curing agent and diluted to 15% with deionized water. Calcium chloride with a mass of 0.25 times that of the wall material was added to the emulsion at a rate of 25 drops / minute through a high-precision metering pump (the flow rate was set to 3 mL / min, and the corresponding drop rate was 25 drops / minute, ±2 drops / minute). At the same time, 0.15 mol / L hydrochloric acid or sodium hydroxide solution was used to adjust the pH value of the reaction system to 6.0 (±0.1). Under the condition of maintaining the temperature at 28°C (±1°C) in an oil bath, a variable frequency stirrer was used to continuously stir at a speed of 180 rpm (±10 rpm) for 3.5 hours. After the reaction was completed, the beads were collected by vacuum filtration (the vacuum degree was controlled at -0.08 MPa, and the filtration time was 15 minutes), and then washed 4 times with anhydrous ethanol. The volume of anhydrous ethanol used for each washing was 3 times the volume of the beads to remove the curing agent and impurities remaining on the surface. After washing, the beads were vacuum dried at 40°C for 2 hours.
[0052] Comparative Example 1
[0053] 1. Material preparation:
[0054] Wall material:
[0055] Ordinary industrial-grade chitosan (deacetylation degree of about 85%) and sodium alginate (viscosity 150-300 mPa·s) were selected and weighed at a mass ratio of 2:3. The chitosan was dissolved in a 1% acetic acid solution that was not purified by secondary distillation. The solution was stirred and dissolved at 50°C and 300 rpm for 2 hours, and the solution was slightly turbid.
[0056] Sodium alginate was dissolved in ordinary distilled water at 40°C and stirred at 250 rpm for 2.5 hours. There was a small amount of insoluble matter in the solution.
[0057] Core material:
[0058] Spearmint oil is extracted by traditional steam distillation and is not refined by molecular distillation.
[0059] Glycerol with a purity of 99% was selected, and spearmint oil and glycerol were directly mixed at a mass ratio of 1:3 at a stirring speed of 250 rpm for 10 minutes. After mixing, the solution had a slight stratification phenomenon.
[0060] (II) Emulsification process:
[0061] The core material was added to the wall material solution, and ordinary emulsification equipment was used. The ratio of the stirring blade diameter to the reaction vessel diameter was 1:4, and the emulsification was stirred at a constant speed of 650 rpm for 15 minutes. There was no temperature and particle size detection and adjustment measures during the emulsification process. The temperature fluctuated around 35°C, and the particle size of the emulsion after emulsification was uneven.
[0062] (III) Curing and molding:
[0063] Undiluted 30% calcium chloride was selected as the curing agent and manually added at an approximate speed of 20 drops / minute. The ratio of the curing agent to the wall material was not precisely controlled, and the pH value of the reaction system was not adjusted. At room temperature (about 25°C), stirring was carried out at a speed of 150 rpm for 3 hours. After the reaction was completed, the beads were collected by natural filtration, rinsed twice with clean water, each time using twice the volume of the beads, and then dried at 50°C under normal pressure for 3 hours.
[0064] Comparative Example 2
[0065] (I) Material preparation:
[0066] Wall material:
[0067] Chitosan and sodium alginate were weighed in a mass ratio of 1:4, and chitosan was dissolved in a 2% acetic acid solution, and stirred and dissolved at 60° C. and 400 rpm for 3 hours.
[0068] Sodium alginate was dissolved in deionized water at 50°C and stirred at 300 rpm for 3.5 hours.
[0069] Core material:
[0070] The spearmint oil is extracted and refined by supercritical carbon dioxide extraction, but the glycerol is selected to have a purity of 99.5%. The spearmint oil and the glycerol are mixed at a mass ratio of 1:2 at a stirring speed of 320 rpm for 15 minutes.
[0071] (II) Emulsification process:
[0072] The core material was added to the wall material solution, and an emulsifying device equipped with a six-blade turbine stirring blade (the ratio of the blade diameter to the reaction vessel diameter was 1:5) was used. The stirring speed was kept constant at 750 rpm, and the emulsification process temperature was set to 40°C, but there was no intelligent speed regulation, precise temperature control, or particle size detection, and the emulsification was performed for 20 minutes.
[0073] (III) Curing and molding:
[0074] 20% calcium chloride was selected as a curing agent and added at a rate of 30 drops / minute. The ratio with the wall material was not precisely controlled. 0.1 mol / L hydrochloric acid or sodium hydroxide solution was used to adjust the pH value of the reaction system to 6.5. At 30°C, it was stirred at a speed of 200 rpm for 4 hours. After the reaction was completed, the beads were collected by vacuum filtration (the vacuum degree was controlled at -0.06MPa, and the filtration time was 10 minutes), washed 3 times with anhydrous ethanol, and the volume of anhydrous ethanol used for each wash was 2.5 times the volume of the beads, and then vacuum dried at 45°C for 2.5 hours.
[0075] Performance test and comparison results:
[0076]
[0077]
[0078]
[0079] Through the above detailed embodiments, comparative preparation processes and performance test comparison results, it can be seen that the preparation method of the present invention has significant advantages in terms of wall material structure, particle size distribution, core material composition and properties, and application performance, and can effectively improve the quality and stability of the small bursting beads of cigarette mouthpieces, and meet the high quality requirements of cigarette production for bursting beads.
[0080] In the production process of cigarette mouthpieces, an automated popping bead implantation production line is used. The production line is equipped with a high-precision visual recognition robotic arm and a high-speed positioning platform. The robotic arm has a repeatability accuracy of ±0.08mm. An elliptical cavity with a diameter of 2.3±0.08mm is pre-set inside the cigarette mouthpiece to accommodate the popping beads. The robotic arm quickly and accurately identifies the position of the mouthpiece cavity through a visual recognition system and implants the popping beads into the cavity at a rate of 60 beads per minute. After the implantation is completed, a thermoplastic polyurethane elastomer is used to seal the mouthpiece cavity opening. The melt index of the thermoplastic polyurethane elastomer is 15g / 10min. The coating operation is carried out at 160°C with a coating thickness of 0.35±0.05mm, ensuring that the popping beads are well sealed inside the mouthpiece and can smoothly release flavor substances when the smoker squeezes the popping beads.
[0081] During the smoking process of cigarettes, when the temperature reaches 320-420℃, the bursting beads can quickly burst and release spearmint oil, bringing a unique cool flavor experience to smokers. The extrusion pressure is monitored in real time by integrating a micro pressure sensor on the cigarette mouthpiece. The accuracy of the pressure sensor is ±0.08N, which can ensure that the bursting beads burst at the appropriate pressure to ensure the flavor release effect. The air permeability of the mouthpiece is adjusted by laser drilling on the circumference of the mouthpiece. The diameter of the micropores is 0.12-0.22mm, and there are 6-9 micropores per square centimeter. Using an air permeability tester, the air permeability of the mouthpiece is between 32-42CU, which helps to release the flavor of the bursting beads while ensuring a good smoking taste.
[0082] In terms of long-term storage, after being stored for 8 months in an environment with a temperature of 26±2℃ and a humidity of 62±5%, sampling inspection showed that the rupture rate of the popping beads was less than 1.5%, and the leakage rate was less than 0.8%. No obvious deterioration occurred, ensuring the high quality and long shelf life of the cigarette products, and effectively improving the market competitiveness of cigarette products.
[0083] In summary, the method for preparing fine bursting beads and the application technology in cigarette mouthpieces of the present invention have formed a complete and efficient system from raw material selection, preparation process optimization to fine design of application links, providing strong support for product innovation and quality improvement in the cigarette industry.
[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing fine explosive beads for cigarette mouthpieces, characterized in that: The preparation method comprises the following steps: First, chitosan and sodium alginate were selected as wall materials, accurately weighed in a mass ratio of 2:3, chitosan was dissolved in 1% acetic acid solution, and dissolved at a temperature of 55°C at a speed of 350 rpm for 2.5 hours, and sodium alginate was dissolved in deionized water, the water temperature was controlled at 45°C, and stirred at a speed of 280 rpm for 3 hours to completely dissolve it, and then the two solutions were mixed and stirred at a stirring speed of 400 rpm for 20 minutes. For the core material, spearmint oil and glycerol were selected and mixed at a mass ratio of 1:3 at a stirring speed of 280 rpm for 12 minutes; Next, the prepared core material was added to the wall material solution, and an emulsification device equipped with a six-blade turbine stirring blade was used, with the ratio of the blade diameter to the reaction vessel diameter being 1:5, and the emulsification was performed at a stirring speed of 700 rpm for 18 minutes, and the temperature during the emulsification process was maintained at 38°C; Subsequently, calcium chloride with a mass 0.25 times that of the wall material was added to the emulsion as a curing agent at a rate of 25 drops / minute, and the pH value of the reaction system was adjusted to 6.
0. The reaction was stirred at 180 rpm at 28°C for 3.5 hours to prepare fine explosive beads with a particle size in the range of 0.5-2.0 mm.
2. The method for preparing fine explosive beads for cigarette mouthpiece according to claim 1, characterized in that: When pre-treating chitosan before mixing with wall materials, the acetic acid solution needs to be purified by secondary distillation, and its purity needs to reach more than 99.5%. During the dissolution process, the temperature is maintained at 55±2°C by a stirring device with temperature feedback, and the stirring speed fluctuation range is controlled within ±15 rpm; For sodium alginate, the water used for dissolution must be ultrapure water treated with ion exchange resin, with a conductivity of less than 2μS / cm. During dissolution, the container must be sealed with a stirring device and the temperature must be maintained at 45±1℃; When mixing two wall materials, a double planetary mixing device is used, the revolution speed of the mixing blade is 420 rpm, the rotation speed is 550 rpm, and the mixing time is precisely controlled at 20±1 minute.
3. The method for preparing fine explosive beads for cigarette mouthpiece according to claim 1, characterized in that: The spearmint oil in the core material is extracted from the spearmint by using a carbon dioxide supercritical extraction method. The spearmint is crushed into 40 meshes and loaded into an extraction kettle. Under the conditions of a pressure of 20 MPa and a temperature of 45° C., carbon dioxide is used as an extractant for extraction for 3 hours. The spearmint oil obtained by the extraction is refined by molecular distillation at a distillation temperature of 70° C. and a pressure of 0.1 kPa. Glycerol should be a food grade product with a purity greater than 99.8%. When mixing spearmint oil and glycerol, a high shear dispersing emulsifier is used to assist stirring at a rotation speed of 3000 rpm and mixing is performed at a stirring speed of 280 rpm for 12±0.5 minutes.
4. The method for preparing fine explosive beads for cigarette mouthpiece according to claim 1, characterized in that: The emulsification equipment is equipped with an intelligent variable frequency speed regulation system. When the emulsion viscosity is in the range of 0.6-1.2 Pa·s, the stirring speed is automatically maintained at 700±25 rpm. When the emulsion viscosity exceeds 1.2 Pa·s, the stirring speed is automatically increased to 750 rpm. The temperature control system of the emulsification equipment adopts fuzzy control algorithm, with a temperature control accuracy of ±0.3℃. The reaction vessel adopts a three-layer jacket structure, with circulating water in the middle layer and insulation materials in the inner and outer layers. At the same time, during the emulsification process, the particle size of the emulsion is tested every 4 minutes. If the particle size deviation exceeds the set range of ±8%, it is corrected by adjusting the stirring speed, temperature or adding an appropriate amount of dispersant.
5. The method for preparing fine explosive beads for cigarette mouthpiece according to claim 1, characterized in that: The concentration of the curing agent calcium chloride is 30%, which needs to be diluted to 15% with deionized water before dropping. During the dropping process, the dropping speed is accurately controlled by a high-precision metering pump. The flow rate of the metering pump is set to 3mL / min, and the corresponding dropping speed is 25±2 drops / minute; After adding the curing agent, the pH value of the reaction system was adjusted to 6.0±0.1 using 0.15 mol / L hydrochloric acid or sodium hydroxide solution. During the reaction, the temperature was maintained at 28±1°C by heating in an oil bath, and a variable frequency stirrer was used to continuously stir at a speed of 180±10 rpm for 3.5 hours; After the reaction was completed, the beads were collected by vacuum filtration with the vacuum degree controlled at -0.08 MPa for 15 minutes, and then washed 4 times with anhydrous ethanol to remove the curing agent and impurities remaining on the surface.
6. The fine bursting beads for cigarette mouthpieces prepared by the method for preparing fine bursting beads for cigarette mouthpieces according to any one of claims 1 to 5 are characterized in that: Scanning electron microscope observation showed that the wall material of the blasting beads showed a regular layered structure, with each layer thickness between 30-50 nanometers. The overall thickness of the wall material was uniform, with an average thickness of 90±12 microns. Under high-resolution microscope observation, there were no holes or defects with a diameter greater than 8 nanometers inside the wall material. The particle size of the blasting beads was tested using a laser particle size analyzer, and the proportion of blasting beads with a particle size range of 0.5-2.0mm reached more than 99%, and the standard deviation of the particle size distribution was less than 0.15mm.
7. The fine explosive beads for cigarette mouthpiece according to claim 6, characterized in that: The content of spearmint oil in the core material of the explosive beads is 25±2%, and the content of glycerol is 75±2%. The core material components are analyzed by gas chromatography-mass spectrometry. The content of carvone in the spearmint oil is 65±3%. The melting point of the core material is -8±2℃ and the boiling point is 190±5℃ as detected by differential scanning calorimeter.
8. The method for applying the fine explosive beads for cigarette mouthpieces according to claims 6-7 to cigarette mouthpieces, characterized in that: In the production process of cigarette mouthpieces, an automated popping bead implantation production line is used, which is equipped with a high-precision visual recognition robot arm and a high-speed positioning platform; The repeatability of the robotic arm is ±0.08mm. An elliptical cavity with a diameter of 2.3±0.08mm is pre-set inside the cigarette mouthpiece to accommodate the popping beads. The robotic arm quickly and accurately identifies the position of the mouthpiece cavity through a visual recognition system and implants the popping beads into the cavity at a speed of 60 beads / minute. After the implantation is completed, the opening of the mouthpiece cavity is sealed with a thermoplastic polyurethane elastomer, the melt index of the thermoplastic polyurethane elastomer is 15g / 10min, the coating operation is carried out at 160°C, and the coating thickness is 0.35±0.05mm.
9. The method for applying fine explosive beads to cigarette mouthpiece according to claim 8, characterized in that: When the smoker squeezes the popping bead, it must break under a pressure of 2.5-3.5N to release the core material. The squeezing pressure is monitored in real time by integrating a micro pressure sensor on the cigarette mouthpiece. The accuracy of the pressure sensor is ±0.08N. The air permeability of the mouthpiece is adjusted by laser punching holes on the circumference of the mouthpiece. The diameter of the micropores is 0.12-0.22mm, and there are 6-9 micropores per square centimeter. The air permeability of the mouthpiece is between 32-42CU when tested with an air permeability tester. It is stored for 8 months at a temperature of 26±2℃ and a humidity of 62±5%. Through sampling inspection, the rupture rate of the popping bead is less than 1.5%, and the leakage rate is less than 0.8%, and no obvious deterioration occurs.